Pediatric Fibrinogen PART I—Pitfalls in Fibrinogen Evaluation and Use of Fibrinogen Replacement Products in Children - Huisman, Elise J.; Crighton, Gemma Louise (Frontiers in Pediatrics, 2021)
Fibrinogen is a key coagulation protein, playing a critical role in hemostasis. It is the first factor to decrease to critical levels during bleeding. Hypofibrinogenemia is an important risk factor for bleeding in clinical settings, including pediatric surgery. Yet, the optimal measurement of fibrinogen levels is subject to debate, as is the critical threshold for intervention. Fibrinogen replacement may be provided by cryoprecipitate and fibrinogen concentrate. Whilst both products contain fibrinogen, they are not equivalent, each has its own advantages and disadvantages, especially for pediatric use. Unfortunately, medical literature to support fibrinogen replacement in children is limited. In this article we review the current diagnostic tools to measure fibrinogen, with respect to their use in the pediatric critical care setting. Secondly, we evaluate the different fibrinogen replacement therapies, focusing on cryoprecipitate and fibrinogen concentrate and examine their individual product characteristics, associated risks and benefits, different dosing strategies and specific pitfalls for use in children. We summarize by highlighting current knowledge gaps and areas for future research.